Can Elephants and Livestock Co-Exist? Solving Grazing Conflicts Through Adaptive Collaborative Management in Southern Kenya (Global Journal of Science Frontier Research, 2019)
Although pastoralism supports many livelihoods in East Africa, and domestic and wild animals have for a long time coexisted in Africa's savannah landscapes, livestock is perceived by conservation authorities as a major threat to the survival of key wildlife species, especially elephants. Drawing on ethnographic data, this study gains local insights from the Maasai pastoralists who live west of Tsavo West and Chyulu Hills National Parks in Kenya on the conflicts surrounding elephant conservation and livestock husbandry in their landscape. The study explored how solving grazing conflicts between the Maasaiand KWS can promote cooperation in elephant conservation. I used narratives from twenty-four key informants and sixty participants in focus group meetings drawn from six villages within Mbirikani, Kuku, and Rombo group ranches which neighbor the parks located in southern Kenya. I also interviewed four park officials working in Tsavo West and Chyulu Hills National Parks about grazing conflicts and collaboration with the Maasai. The views of the Maasai on livestock and wildlife are deeply cultural and differ markedly from those of park officials.
Keywords: kenya; elephants; livestock; conservation; political ecology; maasai adaptive collaborative management